Understanding Earth and Space Science Concepts for Children: A Learning Media “Galaxy Gift” Development - Syarfina Syarfina; Maulidia Maulidia; Ulliyan Dari; Diana Hawary; Enjelina Hendriani; Sri Maisari (Journal of Islamic Education Students (JIES), 2024)
Earth and space science can be learned early with interesting learning methods and media. However, some early childhood institutions must provide attractive and interactive media for learning science. This research aims to develop learning media for children to understand the concepts of earth and space science. This research uses a Research and Development (R&D) approach with tool development & use type of Richey & Klein model consisting of 4 steps: analysis, design, development, and evaluation. The results of the validation of media, language, and early childhood education experts indicate that the learning media named 'galaxy gift' is feasible to develop and become interactive media to increase children's understanding of earth and space science. Field trials show that this media help children to understand about earth and space science concepts and motivate children to learn science. Therefore, this media is very effective as a science learning media for children. For the effectiveness of improving other science concepts in early childhood, further research can be conducted.